Description of pulmonary lesions by Pseudalius inflexus in the porpoise Phocaena spinipinnis - Chavera, Alfonso (2010)
Pulmonary lesions caused by the nematode Pseudalius inflexus (Rudolphi, 1808) Schneider, 1866; in two specimens, male and female of Burmeister's Porpoise (Phocoena spinipinnis Burmeisteir, 1865). The Cetaceans were captured in the Reserva Nacional de Paracas, Peru. Macroscopically, the lung shown superficial harden nodules of 52 cm of diameter and on the cut surface the nematodes were seen surrounded by severe chronic inflammatory reaction and the bronchium are occluded by the cranial part of these parasites and the caudal part remains free. Microscopically, the parasites are shown in different degree of degeneration and they are surrounded by severe inflammatory exudate composed of eosinophils, macrophages, mononuclear cells, multinuclear giant cells and dense granulation tissue scattered by the pulmonary parenchyma with distended and necrotic alveoli. Other lesions included hyperplasia of bronchium mucosa and hyperplasia of the arterial smooth muscle with luminal obliteration. Therefore, a severe eosinophilic granulomatous bronchopneumonia is caused by P. inflexus and is the first description of the parasitic pulmonary lesions in P. spinipinnis.